2018
DOI: 10.1177/1120672118808968
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the effect of intracorneal ring segment in corneal ectasia after laser refractive surgery

Abstract: Purpose: To evaluate the visual, refractive, topographic, pachymetric, and biomechanical outcomes after intracorneal ring segment implantation in corneas with post-LASIK ectasia. Methods: Retrospective longitudinal study enrolling 26 eyes of 22 patients with post-LASIK ectasia and undergoing intracorneal ring segment implantation (KeraRing®, Mediphacos) using a 60-kHz femtosecond laser (IntraLase®, IntraLase Corp.) for corneal tunnelization. Visual, refractive, anterior, and posterior corneal topographic (Pent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Cristina Peris-Martínez et al 14 found statistically significant reduction of sphere (p = 0.043), a significant improvement of UCVA associated (p = 0.019) , a significant reduction of anterior corneal power measurements (p ⩽ 0.014) , steepest posterior keratometric reading (p = 0.006) were observed at 1 month postoperatively, with no significant changes afterwards (p ⩾ 0.133). No significant changes were observed in manifest cylinder (p ⩾ 0.175), BCVA (p ⩾ 0.174), flattest posterior keratometric measurement (p ⩾ 0.282), volumetric measurements (p ⩾ 0.051), and corneal biomechanical parameters (p ⩾ 0.068).…”
Section: Discussionmentioning
confidence: 93%
“…Cristina Peris-Martínez et al 14 found statistically significant reduction of sphere (p = 0.043), a significant improvement of UCVA associated (p = 0.019) , a significant reduction of anterior corneal power measurements (p ⩽ 0.014) , steepest posterior keratometric reading (p = 0.006) were observed at 1 month postoperatively, with no significant changes afterwards (p ⩾ 0.133). No significant changes were observed in manifest cylinder (p ⩾ 0.175), BCVA (p ⩾ 0.174), flattest posterior keratometric measurement (p ⩾ 0.282), volumetric measurements (p ⩾ 0.051), and corneal biomechanical parameters (p ⩾ 0.068).…”
Section: Discussionmentioning
confidence: 93%
“…Differences in refractive behaviour across eyes and between individuals38 39 44 67 73 114 128 are of importance in analyses of dioptric power and the following briefly considers some methods towards qualitatively and quantitatively analysing anisometropia 44 67 73. Anisometropia and aniso-astigmatism are often a consequence of conditions such as keratoconus69 70 85 86 105 123 but can also be an important consideration in refractive42–44 74 87 125 or other surgeries42–44 87–113 sometimes involving IOL36 41–43 45 46 85 99–104 or other implants 89–92 105. Reliability and reproducibility of measures of refractive behaviour are integral to understanding anisometropia 40 57–64 66 109 120–123.…”
Section: Resultsmentioning
confidence: 99%
“… 44 67 73 Anisometropia and aniso-astigmatism are often a consequence of conditions such as keratoconus 69 70 85 86 105 123 but can also be an important consideration in refractive 42–44 74 87 125 or other surgeries 42–44 87–113 sometimes involving IOL 36 41–43 45 46 85 99–104 or other implants. 89–92 105 Reliability and reproducibility of measures of refractive behaviour are integral to understanding anisometropia. 40 57–64 66 109 120–123 Ocular accommodation, 21 22 28 30 31 54–58 62–68 70 73 127 outliers, departures from data normality, laterality and mirror symmetry 67 95 and reflection of cylinder axes 2 11–13 15 17 18 28 67 73 74 must be considered in effective analyses of anisometropia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be considered that although ICRS implantation is safe, suboptimal results are still present in some cases, requiring adjustments and even the explantation of the ring segment [12][13] . Ferrara-type ring segments have been investigated during many years and demonstrated to be a safe option to manage corneal irregularities in a great variety of corneal conditions, including keratoconus [14][15][16][17][18][19][20][21][22][23][24] . It has been even confirmed the histological reversibility of the cornea when the ring segments are explanted [25] .…”
Section: Introductionmentioning
confidence: 99%